A comparative study on magnetic behaviors and magnetocaloric effect in heavy rare-earth antiferromagnetic orthoferrites RFeO3 (R = Dy, Ho and Er). Issue 24 (15th December 2021) - Li, C.L.; Zheng, S.S.; Barasa, G.O.; Zhao, Y.F.; Wang, L.; Wang, C.L.; Lu, Y.; Qiu, Y.; Cheng, J.B.; Luo, Y.S.
Abstract: The heavy rare-earth GdFeO3 -type RFeO3 (R = Dy, Ho and Er) orthoferrites (space group Pnma, N 62) show spin reorientation transition characterized by a turning point on the magnetization curves. The basic Arrott plots curves showing positive slopes confirm the second-order nature of the spin reorientation and the transition temperature T SR is estimated to be ∼45 K, ∼53 K and ∼94 K for DyFeO3, HoFeO3 and ErFeO3, respectively. In addition, magnetic entropy change − Δ S M of the three samples is calculated to be 11.4, 9.8 and 7.4 J kg −1 K −1 at 10 K and 50 kOe, respectively. The field sensitive antiferromagnetic state and competitive magnetocaloric performances in RFeO3 have been attracting considerable interest for the possible applications in spintronic devices.